Transformational leadership: turning university vision into reality / Haliza Mahayuddin - Mahayuddin, Haliza (2010)
Universities have contributed immensely to the success of nation building efforts. Hence, transformation in higher education has become a critical agenda. Today, like other institutions, universities are facing challenges of greater complexity than ever before with relentless pressure of competition while the rate of change is continuously accelerating. Leaving out all the technical analysis, the simple truth is that there is one constant – CHANGE – it is every where and ever present. Much personal pain can be derived from this fact , especially in the resistence to change, or unwillingness to embrace what exists.This has to be resolved within ourselves. This is about how we can transform ourselves to create the reality we desire ( Richard Cox, 2010 ). For universities to be successful and excellent, outstanding leaders are needed who can deliver consistently the highest level of organizational performance combined with an almost obsessive focus on people who can truly understand, embrace and ultimately help implement the changes necessary for the university to thrive in today’s global competitiveness. Outstanding leaders have vision. They share a dream and direction that other people want to share and follow. The leadership vision goes beyond the university’s written organizational mission and vision statement. The vision of leadership permeates the workplace and is manifested in the actions, beliefs, values and goals of the organization’s leaders (Susan Heathfield, 2009). Thus, the need for transformational leadership, an approach that engenders change in individuals and social systems. In its ideal form, it creates valuable and positive change in the followers with the end goal of developing followers into leaders. These leaders display characteristics and competencies that earn trust, instill confidence, and inspire action that results in meaningful and lasting change. Hence, in the quest for excellence, transformation should be effectively supported by understanding and trust, as well as practical initiatives that should enhance competency, creativity and competitiveness among the followers to be able to thrive with full composure, in times of change.